Emergence of BCR–ABL1 Fusion in AML Post–FLT3 Inhibitor-Based Therapy: A Potentially Targetable Mechanism of Resistance – A Case Series - Alotaibi, Ahmad S.; Yilmaz, Musa; Loghavi, Sanam; DiNardo, Courtney; Borthakur, Gautam; Kadia, Tapan M.; Thakral, Beenu; Pemmaraju, Naveen; Issa, Ghayas C.; Konopleva, Marina; Short, Nicholas J.; Patel, Keyur; et al. (Frontiers in Oncology, 2020)
Despite the promising result with FLT3 inhibitors in AML, the emergence of resistance poses a significant challenge, leading to a shorter response duration and inferior survival. This is frequently driven by on-target or parallel pro-survival mutations. The emergence of BCR-ABL1 as a mechanism of possible clonal evolution in relapsed AML has rarely been reported. Here we report our experience with three patients who had emergent BCR-ABL1 fusion at relapse after FLT3 inhibitors-based therapies. The first patient was refractory to multiple lines of therapies, including FLT3 inhibitors-based therapy. Patients #2 and #3 showed some response to combined FLT3 inhibitor and BCR-ABL targeted therapy (gilteritinib and ponatinib). The availability of effective targeted therapies for BCR-ABL1 makes this an important aberration to proactively identify and possibly target at relapse post FLT3 inhibitor therapies.